Síntese, caracterização e estudo da liberação fotoquímica de óxido nítrico por nitrosilo complexos de Ru e Fe e pelo composto [cyclam(NO)4]. - Holanda, Alda Karine Medeiros (2006)
In the present work, a new route was developed for preparing the compound trans-[Fe(cyclam)(NO+)Cl]Cl2, where the nitric oxide is bonding of the iron in the form linear (NO+) with a bond angle Fe-NO at 177,40. The complex was characterized by uv-visible, infrared and electronic paramagnetic resonances spectroscopies, electrochemical techniques and crystal structure determination were undertaken. The study of the photochemical behavior this nitrosyl complex showed the nitric oxide release and appearance of trans-[Fe(cyclam)(H2O)2]3+ species where the compound is irradiated in the λirr=330 nm in aqueous solution pH=3,4. However, when the compound was irradiated in aqueous solution pH=7,04, was observed the reaction of photoreduction and the production of specie trans-[Fe(cyclam)(NO0)Cl]+ (φ=0,4±0,05 mol/einstein). The study of the photochemical behavior of the trans-[Ru(NH3)4L(NO)]Cl3 complexes, where L=ImK2, BzImK2, Caf and Teo showed the nitric oxide production and appearance of trans-[Ru(NH3)4L(Cl)]2+ species, as product of the photolysis in KCl aqueous solution, in the 330-440 nm region when L= ImK2, Caf and Teo and in the λirr=330 nm when L=BzImK2 . The quantum yields (φNO) for this reaction is sensitive to the nature of L, λirr and pH. The lowest quantum yields are found for L=BzImK2 (φNO=0,005±0,0005 mol/einstein) and the higher was observed for the L=Teo (0,68±0,05 mol/einstein). The absence of observable photochemical reaction when these complexes were irradiated on 410-440nm is explained on basis of the changes in character of the lowest energy MLCT band on function of the ligand L. The incorporation of NO in the composition of many molecules is of interest to study the chemical and enzymatic mechanisms of NO release and the pharmacological aspects and biomedical applications of these compounds. Assuming that the N-nitroso compounds belong to a class of NO donors by transferring nitrosyl homolytically or heterolytically to another species, we have performed the nitrosilation reaction of the cyclam species aiming to study the reactivity of a new N-nitrosamine system toward the release of nitric oxide species. The infrared spectrum of [cyclam(NO)4] displays two characteristic bands at 1454 and 1139 cm-1 assigned to the νNO and νNN modes, respectively. The peaks of νN-H observed in the range 3400-3190 cm-1 in the spectrum of thecyclam starting material disappear in the spectrum of [cyclam(NO)4]. Upon white light photolysis of the compound dispersed in KBr, is observed the decrease of the νNO and νNN and of the appearance of a new band at 2228 cm-1, assigned to the νNO+ stretching mode. This indicates that the [cyclam(NO)4] compound under this photolysis conditions behaves as a nitrosyl donor through an heterolytic cleavage of N-NO bond.